Experiencing poetry in the language classroom / Angeline Ranjethamoney Vijayarajoo - Vijayarajoo, Angeline Ranjethamoney (Institute of Research, Development and Commercialization (IRDC), 2005)
This paper looks at the benefits of introducing and using poetry in the language classroom. The authors suggest that students experiencing literature is far more beneficial to L2 learners than just 'studying' it, as is the accepted and traditionally practised approach in exam oriented systems. In the traditonally practised approach of 'studying' literature, the purely linguistic arena is tackled. The authors' suggestion of 'experiencing' Literature involves not only the linguistic but non linguistic arena which will be more enriching ta an individual. This paper makes references to the Theory of Multi-Dimensional Mental Representation which is clearly present in Ll reading and should be encouraged and nurtured in L2 reading. This will very likely achieve more enriching and rewarding outcomes amang L2 learners.